An observational comparative study on the immediate, deferred, and no use of antiepileptics in the management of seizure - Shrestha, Himangi; Krishnan, Athira; Ramaiah, Balakeshwa (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The rationale for starting AEDs in patients with seizure and early epilepsy is still unclear. The decision to start and stop the drugs in patients with single seizures remains controversial. This study aims to compare the efficacy, safety, and short-term outcome of the immediate, deferred, and no use of AEDs in patients presenting with seizure. Methods This observational study, included 87 patients with either gender or age group with first or multiple seizures to investigate immediate, deferred, or no AED use. Detailed demographics, history, and diagnostic test reports were recorded. Drug use patterns and outcomes of seizure recurrence and safety were evaluated. Results: Out of 87 patients (56 male, 31 female), there were 26 paediatrics, 47 adults, and 15 elderly. Immediate AED treatment was given to 75%, 16% deferred, and 9% received no/SOS AED. Levetiracetam was commonly prescribed (78% in ED, 86% in wards, 63% at discharge). For immediate AEDs: 49% had good seizure control, 25% had recurrence, and 9% had breakthrough seizures. Deferred AEDs showed 36% good control/recurrence and 7% breakthrough. Without AEDs: 63% had good control and 25% had recurrence. AEs were higher in the immediate AED group (42%) vs. deferred (15%). Conclusions: The study indicates that immediate use of antiepileptic drugs (AEDs) reduces short-term seizure recurrence but may increase adverse effects. In cases of reversible causes, it may be best to forgo AEDs. Decisions regarding AED therapy should be tailored to the patient’s preferences and risk considerations.